A Study of Evaluation Practices Used for the Students with Hearing Impairment at Internal Level in Special Schools of Punjab - Tayyaba Naz، Rukhsana Bashir، Aneeka Zafar (JIE, 2024)
This descriptive study was aimed to identify the evaluation practices used for the students with hearing impairment at elementary. The major objective of the study was to identify the various evaluation practices used for the students with hearing impairment inside the schools. Research questions were formulated under the light of objectives. The population of the study was the teachers of hearing-impaired students teaching in the special schools of Punjab province.